EFEKTIVITAS PEMBANGUNAN INFRASTRUKTUR DALAM PEMBENTUKAN PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN BULUNGAN KALIMANTAN UTARA - Rahmadan, Rahul; Yuliawati, Witri (Ekonomi Pembangunan Fakultas Ekonomi, 2024)
The purpose of this research is to determine the effectiveness criteria of road infrastructure investment and port infrastructure in the formating GRDP in Bulungan Regency. The period used in this research starts from 2017-2021. It was a Time Series of research on transportation infrastructure investment and Gross Regional Domestic Product (GRDP) in Bulungan Regency, North Kalimantan. The analitycal tool used data used Incremental Capital Output Ratio (ICOR) analysis. Based on the results of the ICOR analysis, the average value ICOR in Bulungan Regency for road infrastructure investment using the transportation sector GRDP at current prices is 7.18 and 0.28 for port infrastructure investment. This shows that investment in road infrastructure is not effective and investment in port infrastructure investment. It showed that road infrastructure investment was no effective, and port infrastructure investment was effective in the formation of GRDP off the transportation sector in Bulungan Regency. Then the average value of ICOR in Bulungan Regency for road infrastructure investment using the GRDP of the transportation sector at constant prices is 0.02 and 0.06 for port infrastructure investment. It showed that road infrastructure investment and port infrastructure investment were effective in forming the GRDP of the transportation sector in Bulungan Regency. For road and port infrastructure investment using GRDP at current prices, the average ICOR value is 27.09 and 1.70, meaning that to increase 1 unit of output, it requires additional capital of Rp. 27.09 for road infrastructure investment and Rp. 1.70 port infrastructure investment. It showed that road investment infrastructure investment was not effective and port infrastructure was effective in the formation of the GRDP of Bulungan Regency. Then for road and port infrastructure investment using GRDP at constant prices, the average ICOR value is -102.93 and -1.65. It indicated that the possibility of investment that occurred in 2020 has not produced output optimally, or it could be said that the investment invested has not been/was not effective in formation of GRDP of Bulungan Regency.